Clonal Propagation Through Nodal Explant Culture of Boerhaavia diffusa L. - A Rare Medicinal Plant - Biswas, A.; Bari, M. A.; Roy, M.; Bhadra, S. K. (Plant Tissue Culture and Biotechnology, 2010)
Multiple shoots were induced on MS fortified with 2.0 mg/l BAP and 0.2 mg/l NAA within 30 days of culture. Maximum (93%) explants produced multiple shoots with an average 12 shoots per culture after two successive subcultures at 14 days interval in the same medium. Cent per cent rooting was achieved in half strength of MS supplemented with 1.0 mg/l IBA. Following 21 days in vitro rooting period and seven days of ex vitro acclimatization, plantlets were successfully established in natural condition. The survival rate of regenerated plants was 90 per cent. Key words: Clonal propagation, Boerhaavia diffusa, Rare medicinal plant, Nodal culture D.O.I. 10.3329/ptcb.v19i1.4917 Plant Tissue Cult. & Biotech. 19(1): 53-59, 2009 (June)